2013
DOI: 10.3892/etm.2013.1433
|View full text |Cite
|
Sign up to set email alerts
|

Onion peel tea ameliorates obesity and affects blood parameters in a mouse model of high-fat-diet-induced obesity

Abstract: The present study examined the effects of onion peel tea (OPT) in a mouse model of high-fat-diet-induced obesity. BALB/c mice were fed a high-fat diet for three weeks, followed by a normal diet with or without OPT for 28 days. OPT suppressed the increases in body weight and level of epididymal fat tissue; it also significantly reduced the serum concentrations of total cholesterol on day 14 and those of glucose and leptin on day 28. The results indicate that OPT has anti-obesity effects in an experimental mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…These results suggest that garlic oil and onion oil have anti-obesity abilities. It has previously been suggested that onion or garlic extract may provide beneficial anti-obesity effects [ 29 , 31 , 32 ]. In this study, the ratio of liver weight to body weight and the ratio of kidney weight to body weight in some intervention groups were significantly higher than those in the HFD-B group.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that garlic oil and onion oil have anti-obesity abilities. It has previously been suggested that onion or garlic extract may provide beneficial anti-obesity effects [ 29 , 31 , 32 ]. In this study, the ratio of liver weight to body weight and the ratio of kidney weight to body weight in some intervention groups were significantly higher than those in the HFD-B group.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were fed with onion peel tea for 28 days after induction of obesity by feeding a high fat diet for 3 weeks. OPT suppressed increase in body weight and level of epididymal fat tissue, reduced serum concentrations of total cholesterol, glucose and leptin [76].…”
Section: Fruits and Vegetablesmentioning
confidence: 92%
“…It was reported that onion reduced insulin resistance and improved FBG levels in MS Zucker type rats [23]. It was shown that onion extract reduced weight gain, epididymal fat accumulation, and serum TC levels in BALB/c mice that were made obese with a high-fat diet [24]. It was reported that a daily onion consumption of 100-120 g significantly decreased TC and LDL cholesterol levels of obese women with polycystic ovary syndrome [25].…”
Section: Root Bulb and Tuber Vegetablesmentioning
confidence: 99%